If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 1) = 1(x + 5) + 1(t + -3) Reorder the terms: 2(1 + 3x) = 1(x + 5) + 1(t + -3) (1 * 2 + 3x * 2) = 1(x + 5) + 1(t + -3) (2 + 6x) = 1(x + 5) + 1(t + -3) Reorder the terms: 2 + 6x = 1(5 + x) + 1(t + -3) 2 + 6x = (5 * 1 + x * 1) + 1(t + -3) 2 + 6x = (5 + 1x) + 1(t + -3) Reorder the terms: 2 + 6x = 5 + 1x + 1(-3 + t) 2 + 6x = 5 + 1x + (-3 * 1 + t * 1) 2 + 6x = 5 + 1x + (-3 + 1t) Reorder the terms: 2 + 6x = 5 + -3 + 1t + 1x Combine like terms: 5 + -3 = 2 2 + 6x = 2 + 1t + 1x Add '-2' to each side of the equation. 2 + -2 + 6x = 2 + 1t + -2 + 1x Combine like terms: 2 + -2 = 0 0 + 6x = 2 + 1t + -2 + 1x 6x = 2 + 1t + -2 + 1x Reorder the terms: 6x = 2 + -2 + 1t + 1x Combine like terms: 2 + -2 = 0 6x = 0 + 1t + 1x 6x = 1t + 1x Solving 6x = 1t + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6x + -1x = 1t + 1x + -1x Combine like terms: 6x + -1x = 5x 5x = 1t + 1x + -1x Combine like terms: 1x + -1x = 0 5x = 1t + 0 5x = 1t Divide each side by '5'. x = 0.2t Simplifying x = 0.2t
| 100-n=51 | | 4sin(2x)-2=0 | | -c+9-6= | | 4x+1-1=7 | | -q=9(q-10) | | 18d-9d-10d+-17d=-20 | | 8x-18=12+3x | | -2x-8=8-10x | | 2x-22.50=10 | | x*y*dx+(x^2-3*y)*dy=0 | | 3v+6v-3(4v-2v)= | | (1-z)(5z-6)=0 | | -.5x=8 | | 50=5/9(f-32) | | .80x=5780 | | 5(-1)-7(-3)= | | 6(p+q)= | | 11t+9t=20 | | 0.17x+0.04(x+3000)=1170 | | -4(-x-16)=-4x-16 | | 3.5d=70d | | N+23=92 | | 20=x/4-2 | | 9y-15= | | 8a-7a=5 | | =6(-6)+30 | | f(.04)=9ln | | sqrt(3x+10)-2=5 | | -0.10(34)+0.25x=0.05(x-12) | | =6(-5)+30 | | 10*n=110 | | 15=02z |